Analisis Biaya Operasional Kendaraan Pada Perusahaan Pengurusan Jasa Kepabeanan - Rahmi Elviana; Lisa Nesti; Reni Desweri Larici (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
Entrepreneur Management Customs Services (PPJK) serves to assist importers or exporters in shipping goods. The indicators of PPJK services are customer satisfaction, timeliness, suitability of quantity and condition of delivery goods. Based on this, distribution is a very important component. Decision making for determining the type of vehicle that will be used to distribute goods requires a comparison between costs and the selection of an appropriate method for making these decisions. The purpose of this study was to analyze the operational costs of PPJK vehicles using Vehicle Operating Cost Analysis (BOK). The conclusion is that the company is advised to use its own delivery vehicle if it has a budget for the purchase of the vehicle. This is because the funds spent on rental costs are greater than operating costs. Based on the calculation of PPJK's Vehicle Operational Costs, the fixed cost of the vehicle is Rp. 325,429,472/year, variable vehicle costs of Rp. 115,579,320/year and other costs of Rp. 43,560,000/year. PPJK was declared eligible to invest in vehicles because the difference between the calculation of the operating costs of the vehicle itself and the rental amounted to Rp. 1,088,910,152, which means the rental cost is higher. In addition, the use of company vehicles can minimize risk factors for work accidents, costs, time and customer satisfaction as long as they have competent human resources. Keywords: BOK, Entrepreneur Management Customs Services, PPJK